The influences of work support and family support on work-family conflict (W-FC) among married female nurses in Shiraz-Iran - Namayandeh, Hajar; Yaacob, Siti Nor; Juhari, Rumaya (Marsland Press, 2010)
The present study highlights the significance of work support (supervisor and coworker support) on work- family conflict. Furthermore, this paper also examines the effects of family support (husband and family members/relatives support) on work-family conflict. The present study highlights the significance of work support (supervisor and coworker support) on work-family conflict. Furthermore, this paper also examines the effects of family support (husband and family members/relatives support) on work-family conflict. This study examines 198 married female nurses in Shiraz-Iran. The findings revealed that low support received from husband, family members/relatives and supervisor might increase perceived conflict between work and family. Unlike previous studies, the finding also indicates that there is no significant relationship between the respondents' support from co-worker with work-family conflict, which may be explained by the specific cultural context in Iran. Implications are discussed and recommendations are made regarding future researches in this area.